Newcastle disease virus fusion protein expressed in a fowlpox virus recombinant confers protection in chickens. - Taylor, J (1990)
A cDNA copy of the RNA encoding the fusion (F) protein of Newcastle disease virus (NDV) strain Texas, a velogenic strain of NDV, was obtained and the sequence was determined. The 1,792-base-pair sequence encodes a protein of 553 amino acids which has essential features previously established for the F protein of virulent NDV strains. These include the presence of three strongly hydrophobic regions and pairs of dibasic amino acids in the pentapeptide Arg-Arg-Gln-Arg-Arg preceding the putative cleavage site. When inserted into a fowlpox virus vector, a glycosylated protein was expressed and presented on the surface of infected chicken embryo fibroblast cells. The F protein expressed by the recombinant fowlpox virus was cleaved into two polypeptides. When inoculated into susceptible birds by a variety of routes, an immunological response was induced. Ocular or oral administration of the recombinant fowlpox virus gave partial protection, whereas both intramuscular and wing-web routes of inoculation gave complete protection after a single inoculation.